Promosi Penjualan dan Potongan Harga terhadap Impulsive Buying pada Social Commerce - Widya Putri Fridayanti; Suratno Suratno (Intitut Agama Islam Nasional Laa Roiba Bogor, 2026)
The development of social commerce has driven an increase in impulsive buying behavior among consumers, particularly in interactive, content-based digital shopping environments supported by instant transaction features. The characteristics of social commerce, which combine social interaction, recommendations, and limited-time promotions, make consumers more susceptible to unplanned purchasing decisions. Numerous empirical studies have shown that sales promotions and discounts are two marketing stimuli that significantly trigger impulsive buying. However, studies that comprehensively synthesize and compare the consistency of findings related to these two variables in the context of social commerce are still relatively limited. This study aims to systematically compare the impact of sales promotions and discounts on impulsive buying behavior in social commerce through a Systematic Literature Review (SLR) approach following the PRISMA 2020 protocol. Articles for review were selected based on specific inclusion and exclusion criteria. A total of 28 articles that met the inclusion criteria were analyzed using a descriptive-comparative synthesis approach. The articles used were national or international scientific articles written in English or Indonesian, and published between 2020 and 2025 in Google Scholar or Scopus. The synthesis results show that both variables generally have a positive and significant impact on impulsive buying, but price discounts exhibit a higher level of consistency in their influence compared to sales promotions. These findings provide insight into consumer behavior in social commerce, offering valuable references for digital marketing strategies.